Sensitive Cu2+ detection by reversible on-off fluorescence using Eu3+ complexes in SiO2, in chitosan/polyethylene oxide nanofibers - Wang, Xiaozhen; Wang, Yanxin; Huang, Linjun; Li, Bingyang; Yan, Xianhang; Huang, Zhenzhen; Wang, Yao; Kipper, Matt J.; Tang, Jianguo (Materials & design, 2021)
CH/PEO-SiO2@Eu3+ fiber is prepared by electrospinning. Due to the fluorescence of Eu3+ complex, the film appears red under the excitation of UV-light. When the Cu2+ solution is dropped to the film, the color of the film will no longer appear red, and the fluorescence of the composite chitosan nanofibers can be quickly and sensitively quenched. [Display omitted] •CH/PEO-SiO2@Eu3+ nanofiber is prepared by electrospinning.•Due to the fluorescence of Eu3+ complex, the film appears red under the excitation of UV-light.•The fluorescence of the CH/PEO-SiO2@Eu3+ film can be quenched after Cu2+ solution is dropped on it. Trace amounts of heavy metal ions in the human body are essential for maintaining health. However, heavy metal ion excess or deficiency causes toxicity or disease. This study examines the sensitivity of luminescent europium complexes for the detection of Cu2+. Here, Eu3+ is complexed with1,10-phenanthroline (phen) and 4,4′,4-trimethyltriphenylamine (TTA) to form luminescent [Eu3+(TTA)3phen] complexes, encapsulated in silica (SiO2) nanoparticles. The silica nanoparticles are then formed into a composite with a blend of chitosan and polyethylene oxide (PEO), to make electrospun nanofibers. The combination of Eu3+ complexes with SiO2 nanoparticles doped in chitosan enhances the fluorescence performance. Photophysical measurements show that when the Cu2+ concentration is 100 μmol/L, the fluorescence of the composite chitosan nanofibers can be quickly and sensitively quenched, and that concentrations as low as 10 μmol/L Cu2+ can be detected. Furthermore, the use of chitosan and PEO to prepare the material makes these new fluorescence-based copper sensing materials suitable for Cu2+ detection in biological systems.